Enhance Manage Regulation Restorative Justice For Solving Community Conflict - Mhd. Azhali Siregar; Rahul Adrian Fikri (Sean Institute, 2022)
Customary law has long been ignored by our society because we are too enthusiastic about the criminal and civil laws adopted since the Indonesian colonial era. Although so-called modern law cannot limit the limits of its application in various regions throughout Indonesia, customary law can be a sizeable substitute. Theoretically, this can be applied formally in various regions in Indonesia as such by fulfilling several criteria by the principles used by national law. The major change in the orientation of criminal law is the shift in the concept of justice, from justice based on retaliation to justice that is restorative. Protection and restoration of the rights of victims and the general public are seen as important as sentencing and/or rehabilitation of perpetrators of crimes. Based on the Republic of Indonesia Police Regulation No. 8 of 2021 concerning the Handling of Criminal Acts Based on Restorative Justice, the aim is to realize the case settlement process does not only aim solely to punish or embarrass someone, but rather to attempt to obtain truth that is useful to help restore disharmonious relations between perpetrators, victims, and society.